Failure analysis of a damaged direct injection diesel engine piston - Caldera, Martin (2017)
This work deals with the piston failures found in diesel engines functioning in light trucks. The failure was a hole inside the bowl located at the top of the piston, which is the combustion chamber of the engine. This hole progressed and finds its way out between the second and third rings. The operational characteristics of the engine were analyzed in order to elucidate the probable acting failure mechanisms. For the evaluation, obviously were assessed the damaged pistons but also pistons of the same engine without the mentioned failure and a new piston. Different studies and measurements were carried out such as microstructural morphologies and transformations, hardness, fracture surface analysis and chemical composition. The piston design, the material used and the operational conditions (thermal and mechanical) were studied with the purpose of determining the failure origin. It was concluded that thermomechanical fatigue along with some degree of degradation suffered by the material is responsible of the reported failure.